External borrowing, capital formation and growth in developing countries - Rainer Erbe (Intereconomics, 1984)
Since the summer of 1982 the banking community has been faced with an international debt crisis of unprecedented dimensions. The debt rescheduling agreements that have been negotiated since then involve sums totalling no less than 100 billion. However, they give the international financial system no more than a breathing-space. The following two articles deal with different aspects of this crisis. Rainer Erbe examines the question as to what growth effects were associated with external borrowing. Can a lack of growth effects be made responsible for the crisis or were other factors more important? This is followed by an article by Anton Konrad who discusses the proposals which have been made for long-term crisis management. What are their chances of success?
Keywords: 330; Debt Crisis